INVESTIGATING UNIDIMENSIONALITY OF MATHEMATICS MULTIPLE-CHOICE TEST ITEMS USED FOR JOINT MOCK EXAMINATION IN KWARA STATE PUBLIC SCHOOLS - Idris Mohammed Jimoh; Joseph Taiwo Akinboboye; Adaramaja Lukman Sheu (Universitas Ahmad Dahlan, 2021)
Mathematics is an essential subject for human existence on day-to-day activities. This is an indication that it if properly handed it could enhance national development. Therefore, in test items construction to examine students performance in the subject careful considerations must be given. The purpose of the study is to investigate unidimensionality of mathematics multiple-choice test items used for a joint mock examination in Kwara State public schools. The study adopted a descriptive research survey type. The population comprised students in Senior Secondary Schools while the target population consisted of Senior Secondary School II students. The multistage sampling technique that involved stratified, proportionate and simple random sampling was used at different stages of selections. The measuring device was the 2018/2019 Kwara State Joint Mock Mathematics Test. The test is a standardized test and thus the validity and reliability coefficients were not disclosed to the public. The statistical technique employed was factor analysis using SPSS 25.0 version. Tetrachoric correlation statistic was used to obtain 0.96 reliability coefficient. This study, therefore, concluded that only 41 (82%) of 50 multiple-choice items revealed evidence of unidimensionality. One of the recommendations was that those items that violated unidimensionality assumption should be revisited so that instrument could be 100% compliance to unidimensionality.